Determination of surface potential of kaolinite for selection of optimal enhancement pattern for removal of heavy metal contaminant in electrokinetics remediation - V. R. Ouhadi; M. A. Farahpour; F. Faridi; S. Gohari (مهندسی عمران شریف)
Buffering capacity measurement is one of the standard methods to evaluate contaminant retention by soil or the selection of enhancement methods for contaminant removal. However, due to the limitations of this experiment, the quantitative use of the results of this experiment involves noticeable errors. The main objective of this paper is to present theoretical and practical insights into zeta potential theory to optimize the removal of heavy metal contaminants from clayey soils. This is achieved by aligning the direction of electro-osmosis flow with the ion migration phenomenon. Based on the results of this paper, with the determination of variation of the surface potential of clay at different geo-environmental conditions, the curve of zeta potential can be divided into three zones, which are called retention, stable, and desorption sections. Based on these three different areas, with a selection of optimum enhancement patterns, one can align the direction of electro-osmosis flow with the ion migration phenomenon. Consequently, more uniform removal of heavy metals will be achieved, and the efficiency of the electrokinetics method will increase. Finally, it is shown that using a fundamental aspect of the surface potential of clays with the concept of different retention phases of a contaminant in the soil is an applicable and theoretical method for optimized contaminant removal from clayey soils.